2016
DOI: 10.1016/j.cogdev.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The ring that does not bind: Topological class in infants’ working memory for objects

Abstract: Infants and adults are highly sensitive to objects' topology (geometrical invariance under stretching). Indeed, topological class information may form the essential core of object representations. We tested this hypothesis by studying 6-month-old infants, who can remember the existence of multiple objects but are limited to remembering the featural identity (e.g. shape or color) of only one object. In two experiments, after hiding two topologically distinct objects separately, we revealed one of the objects to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…First, infants of this age have previously been shown to successfully infer agents’ goals from their preferential reaching behavior (Luo & Baillargeon, ; Woodward, ) and to make gaze predictions based on agents’ goals (Kim & Song, ; Kochukhova & Gredebäck, ), albeit with some variability (Gredebäck et al., ). Second, and most importantly, 6‐month‐olds’ ability to maintain representations of two occluded objects (in the absence of a social agent) is well understood (Káldy & Leslie, ; Kibbe & Leslie, , , in press). In these studies, infants were familiarized with two featurally distinct objects (e.g., a disk and a triangle) placed sequentially on an otherwise empty stage.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…First, infants of this age have previously been shown to successfully infer agents’ goals from their preferential reaching behavior (Luo & Baillargeon, ; Woodward, ) and to make gaze predictions based on agents’ goals (Kim & Song, ; Kochukhova & Gredebäck, ), albeit with some variability (Gredebäck et al., ). Second, and most importantly, 6‐month‐olds’ ability to maintain representations of two occluded objects (in the absence of a social agent) is well understood (Káldy & Leslie, ; Kibbe & Leslie, , , in press). In these studies, infants were familiarized with two featurally distinct objects (e.g., a disk and a triangle) placed sequentially on an otherwise empty stage.…”
mentioning
confidence: 99%
“…Infants’ representations of these objects were examined by removing one of the occluders and revealing either the original hidden object or the unexpected other object, and measuring infants’ looking times to these outcomes. This method has shown that, when objects are featurally distinct, 6‐month‐old infants represent the featural identity of the object that was hidden last , looking longer when the object is revealed to have changed (Káldy & Leslie, ; Kibbe & Leslie, ). However, 6‐month‐olds consistently fail to remember the featural identity of the object that was hidden first (Káldy & Leslie, ; Kibbe & Leslie, , in press).…”
mentioning
confidence: 99%
See 3 more Smart Citations